INCREASING CONCEPT ACQUISITION OF JUNIOR SECONDARY SCHOOL STUDENTS THROUGH CHEMISTRY LOCAL CONTENT PROGRAM BASED ON THE â€œORANG LAUTâ€ - Basuki, Ari (JURNAL PENDIDIKAN SAINS DAN APLIKASINYA, 2020)
Research about the implementation  of  local content program based on the ?Orang Laut? culture to increase concept acquisition of 8th grade student has been done. The purpose of this research to increase of chemistry concept acquisition junior secondary school students at chemistry learning, by applying of chemistry local content program based on the ?Orang Laut? culture. Research conduct used quasi-experiment method. Research subjects were 8th grade students in Tanjungpinang city that consist of 99 and 94 students on experiment and control groups, respectively. Score of acquisition concept collected by validated test instrument.  Pretest and posttest scores used to calculate of normalized gain (N-gain) average of experiment and control groups. To compare the increasing of  concept acquisition on the experiment and control class conduct by statistical t-test with ?=0,05. The research result indicated that applying of chemistry local content program based on the ?Orang Laut? culture at chemistry  learning could  increase of chemistry concept acquisition junior secondary school students, better than conventional chemistry learning. The difference of  concept acquisition increase on the  experiment and control groups is significant ( tcalc = 8,895; p=0,000) with  average of N-gain percent  were 43 and 20 in the middle and low categories, respectively.  Increasing  of  concept acquisition at  experiment group on the label concept of matter characteristics is highest  and the label concept of matter particles is lowest with N-gain average by 44 and 26 percent, respectively.